The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.chemphys.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Coherent wavepacket motion in an ultrafast electron transfer system monitored by femtosecond degenerate four-wave-mixing and pump–probe spectroscopy

Abstract: Coherent nuclear wavepacket motions were monitored by three types of femtosecond time-resolved spectroscopy, namely, transient absorption measurement utilizing white-light supercontinuum (WC-TA), degenerate four-wave-mixing (DFWM), and pump-probe (PP) measurements, for an ultrafast intermolecular electron transfer (ET) system with a dye molecule, oxazine 1 (Ox1), dissolved in an electron donating solvent, N,N-dimethylaniline (DMA). Vibrational frequencies of the wavepacket motion in the excited and in the grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Upon excitation, the electron density is removed from the bonds of the conjugated π-system, effectively weakening the classical “spring constant” and lowering the energy of the vibrational modes in the excited state. As a result, the Raman spectrum of the excited state is red-shifted compared to the ground-state Raman spectrum, an effect which has been reported previously in a similar system, oxazine 1 . The Raman spectrum extracted from the resonant pump data indicates that the coherence originates from an excited-state wavepacket and agrees with the position of the phase-flips at λ max *abs and λ max fl .…”
Section: Resultssupporting
confidence: 84%
“…Upon excitation, the electron density is removed from the bonds of the conjugated π-system, effectively weakening the classical “spring constant” and lowering the energy of the vibrational modes in the excited state. As a result, the Raman spectrum of the excited state is red-shifted compared to the ground-state Raman spectrum, an effect which has been reported previously in a similar system, oxazine 1 . The Raman spectrum extracted from the resonant pump data indicates that the coherence originates from an excited-state wavepacket and agrees with the position of the phase-flips at λ max *abs and λ max fl .…”
Section: Resultssupporting
confidence: 84%
“…In the Ox1/DMA system, the observation of persistent oscillatory features in pump-probe measurements spurred debates on whether PET involved the coherent transfer of an electron and to what extent this was mediated by molecular vibrations and solvent interactions. While PET remains a poor fit for the cresyl violet and tetrazine system, the excitation dependence of the new ESA peak at 425 THzlocated only at excitations above 550 THzsuggests that molecular vibrations and solvent mediation play an important role, pointing to ESPT as a possible mechanistic pathway for the fluorescence quenching. In the cresyl violet and tetrazine system, the two exocyclic amine/iminium groups of cresyl violet can act as weak photoacids, while tetrazine can be considered a weak photobase that mediates ESPT to the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, Bixon and Jortner modeled the coherence effects in nonadiabatic ET and proposed that the observed oscillations in a charge transfer complex are not vibrationally coherent product formation, rather it comes from the initial state . Various experiments were further conducted including transient IR, stimulated Raman, and 2D spectroscopies, ,, in addition to pump–probe measurement in the visible range. , , A recent femtosecond X-ray scattering study suggested that the coherent translational motions of a solvent mediate the ultrafast intramolecular ET in a mixed-valence bimetallic complex through hydrogen bonding between a solvent and solute . However, it is still challenging to distinguish which vibrations are coupled to a reaction and which ones are merely “spectator modes”, because the number of Franck–Condon active vibrations observed by ultrafast spectroscopy is usually quite large, encompassing the absorbers Raman-active modes .…”
Section: Introductionmentioning
confidence: 99%